A higher bacterial inward BCAA transport driven by Faecalibacterium prausnitzii is associated with lower serum levels of BCAA in early adolescents - Sofia Moran-Ramos; Luis Macias-Kauffer; Blanca E. López-Contreras; Hugo Villamil-Ramírez; Elvira Ocampo-Medina; Paola León-Mimila; Blanca E. del Rio-Navarro; Omar Granados-Portillo; Isabel Ibarra-Gonzalez; Marcela Vela-Amieva; Armando R. Tovar; Nimbe Torres; et al. (BMC, 2021)
Abstract Background Elevations of circulating branched-chain amino acids (BCAA) are observed in humans with obesity and metabolic comorbidities, such as insulin resistance. Although it has been described that microbial metabolism contributes to the circulating pool of these amino acids, studies are still scarce, particularly in pediatric populations. Thus, we aimed to explore whether in early adolescents, gut microbiome was associated to circulating BCAA and in this way to insulin resistance. Methods Shotgun sequencing was performed in DNA from fecal samples of 23 early adolescents (10-12 years old) and amino acid targeted metabolomics analysis was performed by LC-MS/MS in serum samples. By using the HUMAnN2 algorithm we explored microbiome functional profiles to identify whether bacterial metabolism contributed to serum BCAA levels and insulin resistance markers. Results We identified that abundance of genes encoding bacterial BCAA inward transporters were negatively correlated with circulating BCAA and HOMA-IR (P < 0.01). Interestingly, Faecalibacterium prausnitzii contributed to approximately ~ 70% of bacterial BCAA transporters gene count. Moreover, Faecalibacterium prausnitzii abundance was also negatively correlated with circulating BCAA (P = 0.001) and with HOMA-IR (P = 0.018), after adjusting for age, sex and body adiposity. Finally, the association between Faecalibacterium genus and BCAA levels was replicated over an extended data set (N = 124). Conclusions We provide evidence that gut bacterial BCAA transport genes, mainly encoded by Faecalibacterium prausnitzii, are associated with lower circulating BCAA and lower insulin resistance. Based on the later, we propose that the relationship between Faecalibacterium prausnitzii and insulin resistance, could be through modulation of BCAA.